(untitled) (Journal of Obstetrics and Gynaecology of Eastern and Central Africa, 2021)
Background: Vaginal birth after cesarean (VBAC) is rarely offered as a delivery option, for gravid women with more than two cesarean deliveries, due to the increased risk of adverse fetal and maternal outcomes. Case presentation: A 38-year-old Para 4+0 Gravida 5 who had had four previous cesarean deliveries was admitted in the second stage of labor in Maragua sub- county hospital. She delivered a live male infant by spontaneous vaginal delivery with no complications. She had an open bilateral tubal ligation on day two post-delivery and was discharged on day three post-bilateral tubal ligation. Conclusion: Vaginal delivery after cesarean delivery, while not recommended, is possible even in patients who have had multiple caesareans deliveries. Patient sensitization about antenatal care and involvement in their birth plans should also be prioritized.